E-Sports Phenomenon and Physical Education: A Social Study on the Shifting Meaning of Sports Activities - Muhammad Aprilyansyah Pratama Rusli; Andi Fathir Prawira R; Andi Ridwan; Muh. Adnan Hudain; Alimin Alwi (Jurnal Ilmiah Multidisiplin, 2025)
The development of technology and digitalization has given rise to a new phenomenon in the world of sports—e-sports—which shifts the concept of sports from physical activities to the virtual realm. This study aims to analyze the position of e-sports within the context of physical education and its implications for the changing meaning of physical activity from a socio-cultural perspective. The research employs a qualitative method with a descriptive approach through literature review, academic articles, and relevant previous studies. The findings indicate that although e-sports do not require intensive physical activity, they possess competitive characteristics similar to traditional sports, particularly in aspects of strategy, sportsmanship, and teamwork. The popularity of e-sports among younger generations presents both challenges and opportunities for physical education to integrate digital literacy, 21st-century skills, and values of sportsmanship without neglecting the importance of physical health. Socio-culturally, e-sports reflect the dynamics of digital society while reaffirming that the meaning of sports is dynamic and contextual. Therefore, educators, communities, and the government need to play an active role in guiding the development of e-sports to maintain a balance between physical, educational, and achievement dimensions.